An Aluminium Imide as a Transfer Agent for the [NR]2− Function via Metathesis Chemistry. Issue 20 (27th February 2023) - Heilmann, Andreas; Vasko, Petra; Hicks, Jamie; Goicoechea, Jose M.; Aldridge, Simon
Abstract: The reactions of a terminal aluminium imide with a range of oxygen‐containing substrates have been probed with a view to developing its use as a novel main group transfer agent for the [NR] 2− fragment. We demonstrate transfer of the imide moiety to [N2 ], [CO] and [Ph(H)C] units driven thermodynamically by Al−O bond formation. N2 O reacts rapidly to generate the organoazide DippN3 (Dipp=2, 6‐ i Pr2 C6 H3 ), while CO2 (under dilute reaction conditions) yields the corresponding isocyanate, DippNCO. Mechanistic studies, using both experimental and quantum chemical techniques, identify a carbamate complex K2 [(NON)Al‐κ 2 −(N, O)−N(Dipp)CO2 ]2 (formed via [2+2] cycloaddition) as an intermediate in the formation of DippNCO, and also in an alternative reaction leading to the generation of the amino−dicarboxylate complex K2 [(NON)Alκ 2 −(O, O′)−(O2 C)2 N‐(Dipp)] (via the take‐up of a second equivalent of CO2 ). In the case of benzaldehyde, a similar [2+2] cycloaddition process generates the metallacyclic hemi‐aminal complex, K n [(NON)Alκ 2 −(N, O)−(N(Dipp)C(Ph)(H)O] n . Extrusion of the imine, PhC(H)NDipp, via cyclo‐reversion is disfavoured thermally, due to the high energy of the putative aluminium oxide co‐product, K2 [(NON)Al(O)]2 . However, addition of CO2 allows the imine to be released, driven by the formation of the thermodynamically more stable aluminium carbonate co‐product, K2 [(NON)Al(κ 2 −(O, O′)−CO3 )]2 . Abstract : Reactions of a terminal aluminium imide with oxygen‐containing substrates are probed with a view to developing its use as a transfer agent for the [NR] 2− fragment. We demonstrate transfer of the imide moiety to [N2 ], [CO] and [Ph(H)C] fragments to give organo‐azide, ‐isocyanate and ‐imine products, driven thermodynamically by Al−O bond formation.